OPTIMALISASI POSYANDU REMAJA PERSPEKTIF STRUKTURASI GIDDENS DALAM MENCEGAH PERKAWINAN ANAK DI JEPARA - Sadid, Muhammad Arfin; Choeri, Imron; Rosyada, Amrina (IAIN BONE, 2024)
This article discusses the optimization of Posyandu Remaja which is a Jepara Regency Regional Government program. This research aims to analyze the role of Posyandu Remaja in improving adolescent life skills and its potential in delaying child marriage using Giddens' structuration theory approach. This research uses qualitative methods with a sociological approach, located in several villages in Jepara Regency. Data was obtained through interviews, observation and documentation. The research results show that optimizing the role of Posyandu Remaja Â can be achieved through increasing socialization, innovative activities, and delivering more relevant material. By actively involving teenagers in activities, this program can be more effective in supporting youth empowerment and delaying marriage until a more mature age.